2020
DOI: 10.1002/chem.202002554
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Towards αVβ6 Integrin Ligands Using Novel Aminoproline‐Based Cyclic Peptidomimetics

Abstract: In recognition of the key role played by integrins in several life-threatening dysfunctions,t he search for novel small-molecule probes that selectively recognize these surface receptors is still open and widely pursued. Inspired by previously established aminoproline (Amp)-RGD based cyclopeptidomimeticswith attracting a V b 3 integrin affinity and selectivity,t he designa nd straightforward synthesis of 18 new AmpRGD chemotypes bearinga dditional structuralv ariants were herein implemented, to shift toward pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 42 publications
(107 reference statements)
0
14
0
1
Order By: Relevance
“…Nonetheless, while many ligands are available for αIIbβ3, αvβ3, and α5β1, 28 37 few selective binders are known for αvβ6 and αvβ8. 38 43 In this regard, we recently identified a cyclic pentapeptide, namely, [RGD-Chg-E]-CONH 2 ( 1 ) ( Chart 1 ), as a potent and preferential αvβ6 ligand, 39 which was successfully converted into an effective probe for molecular imaging. 42 Considering that herpesviruses employ both αvβ6 and αvβ8 as co-receptors for cellular entry, a dual ligand of these integrins should represent a more efficient anti-HSV agent than the corresponding mono-αvβ6- or αvβ8-selective binders.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, while many ligands are available for αIIbβ3, αvβ3, and α5β1, 28 37 few selective binders are known for αvβ6 and αvβ8. 38 43 In this regard, we recently identified a cyclic pentapeptide, namely, [RGD-Chg-E]-CONH 2 ( 1 ) ( Chart 1 ), as a potent and preferential αvβ6 ligand, 39 which was successfully converted into an effective probe for molecular imaging. 42 Considering that herpesviruses employ both αvβ6 and αvβ8 as co-receptors for cellular entry, a dual ligand of these integrins should represent a more efficient anti-HSV agent than the corresponding mono-αvβ6- or αvβ8-selective binders.…”
Section: Introductionmentioning
confidence: 99%
“…High resolution mass analysis (ESI) was performed on LTQ ORBITRAP XL Thermo apparatus and are reported in the form of ( m / z ). (2 S ,4 S )-4- N -(9-Fluorenylmethoxycarbonyl)aminoproline ( 20 ) and 4-[[[(2-methylphenyl)amino] carbonyl]amino]phenylacetic acid (MPUPA-OH) ( 21 ) were prepared according to the literature procedures [ 22 , 32 ].…”
Section: Methodsmentioning
confidence: 99%
“… Amp-based cyclopeptides directed to RGD-recognizing α V β 3 , α V β 5 , and α V β 6 integrins (compounds 5 and 6 ) [ 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ], and general structure of cyclopeptidomimetics 7 designed and synthesized to target α 4 β 1 integrin in the present study. …”
Section: Figures Schemes and Tablementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, George and colleagues suggested that novel antifibrotic drugs targeting α V β 6 may prevent the development of severe SARS‐CoV‐2 infection. [17] Potent and selective α V β 6 integrin ligands have been recently published in literature, [18] such as the nonapeptide α V β 6 antagonist c [FRGDLAFp(NMe)K] (I, Figure 1 ), [19] the cyclopeptide c (RGD‐Chg‐E)‐CONH 2 (II, Figure 1 ), [20] the peptidomimetic c (Amp)LRGDL (III, Figure 1 ) [21] and the non‐peptidic small‐molecule inhibitor developed by GSK (IV, GSK3008348, Figure 1 , discussed in the following paragraph). [22] …”
Section: Targeting α V β 6 For the Inhibition Of Sars‐cov‐2 Entrymentioning
confidence: 99%